Condensation Behavior of Ag Aggregates on Liquid Surfaces - 张晓飞 张初航 吕能 谢建平 叶高翔 (Chinese physics letters, 2010)
We report a condensation behavior of silver aggregates on silicone oil surfaces. The deposited Ag atoms diffuse and aggregate on the oil surface, and then form granular clusters and ramified islands. The apparent Ag coverage of the total area increases linearly with the nominal film thickness h for h 〈 0.9nm. However, the coverage exhibits a fluctuation behavior for 1.0 nm 〈 h〈 2.5 nm. It is found that the anomalous behavior of the coverage is resulted from a characteristic material condensation process in the aggregates.